1989
DOI: 10.1002/eji.1830190120
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ribosylation of pertussis toxin substrates and inhibition of peptidoglycan‐, muramyl dipeptide‐ and lipopolysaccharide‐induced mitogenic stimulation in B lymphocytes

Abstract: Selective inhibition by pertussis toxin (PT) of mitogenic activation of mouse B lymphocytes by bacterial mitogens (peptidoglycan and lipopolysaccharide) and muramyl dipeptide (a synthetic analog of peptidoglycan fragment) was demonstrated. Mitogenic activation of B cells by protein kinase C activators and ionomycin was insensitive to PT. Also PT did not inhibit peptidoglycan- and lipopolysaccharide-induced differentiation of B cells into Ig-secreting cells, when it was added to the cultures after the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This hypothesis was further supported by the results that LTA-stimulated p42/ p44 MAPK phosphorylation was attenuated by transfection with human dominant negative mutant of TLR2 plasmid. Moreover, LPS-stimulated cellular responses have been shown to be mediated through a G i or G q protein coupling process in several cell types (10,31). This is confirmed by our observation that the LTA-stimulated p42/p44 MAPK phosphorylation was significantly attenuated by PTX but not by CTX.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This hypothesis was further supported by the results that LTA-stimulated p42/ p44 MAPK phosphorylation was attenuated by transfection with human dominant negative mutant of TLR2 plasmid. Moreover, LPS-stimulated cellular responses have been shown to be mediated through a G i or G q protein coupling process in several cell types (10,31). This is confirmed by our observation that the LTA-stimulated p42/p44 MAPK phosphorylation was significantly attenuated by PTX but not by CTX.…”
Section: Discussionsupporting
confidence: 86%
“…LPS has been shown to be linked to a pertussis toxin (PTX)-sensitive G protein (10). To determine whether the effect of LTA on p42/p44 MAPK activation was mediated by a receptor coupled to a PTXsensitive G protein, the cells were pretreated with 100 ng/ml of PTX for 24 h and then stimulated with 50 g/ml of LTA for 7 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even less is known about the early intracellular events that mediate LPS responses. Several investigators have reported that LPS activates a pertussis toxin-sensitive guanine nucleotidebinding protein (G protein) (6)(7)(8)(9). However, some LPS actions in cells are unaffected by pertussis toxin treatment (refs.…”
mentioning
confidence: 99%
“…Cells (1.5 x 106 per well in six-well plates) were labeled for 18 hr in 1.5 ml of growth medium containing 0.5 ,uCi of [5,6,8,9,11,12,14,15(n)-3H]20:4 (specific activity, 60-100 Ci/ mmol; DuPont/NEN). After washing in situ with PBS and addition of fresh growth medium, the cells were pretreated for 4 hr with the indicated concentration of herbimycin A.…”
mentioning
confidence: 99%